PENERAPAN METODE WAFA DALAM PEMBELAJARAN PENGENALAN AL-QUR’AN PADA ANAK KELOMPOK A TKIT AL-MUMTAZ PONTIANAK - Dwiyanti, Devi; Ali, Muhamad; R, Marmawi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to defermine application of the Wafa method in learning the introduction of the Qur?an in group A children in the integrated Islamic Kindergarten Al-Mumtaz Pontianak. The research method used in this study is a qualitative method with the type of phenomenological research. The subject of this research is the homeroom teacher A and the children of class A. The data collection techniques of this research are observation, interviews, and documentation techniques. The results of this research are the application of the Wafa (Tilawah and Tahfidz) method in learning the introduction of the Qur?an to group A children in the Al-Mumtaz Integrated Islamic Kindergarten Pontianak using the 5P method (opening, introduction, learning, assessment, and closing). In the application of the 5P method there are still teachers who skip parts such as not repeating learning delivered at the time of closing. Specifically for Tahfidz the application is also carried out in the morning before starting the activity and during the day after the midday prayer. As a result of the application of Wafa, there is an increase in each phase. The implication is that the teacher has applied Wafa learning well, but there are still teachers who have not fully implemented the parts of their learning.Keywords: Application of Wafa Method, Learning Introductin of Al-Qur?an